2021
DOI: 10.51791/njap.v41i2.2399
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of growth response and genetic parameter estimates of some quantitative traits in three broiler strains in South-West, Nigeria

Abstract: A total of 150 pure strain broiler chicks comprising 50 each of Arbor Acre, Marshall and Ross were used for this experiment which lasted 10 weeks at the Poultry Breeding Unit of the Directorate of University Farms (DUFARMS) of the Federal University of Agriculture, Abeokuta (FUNAAB), Ogun State Nigeria. The experiment was carried out to make comparative analyses of growth response and genetic parameter estimates of some quantitative traits (Body weight and linear body measurement) in Arbor Acre, Marshall and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…The moderate to fairly high heritability and repeatability estimates obtained at 4 weeks for both sexes showed that environmental influence on these traits was reduced compared to the results obtained at 2 weeks of age. The heritability estimates obtained in this study were higher than what Sanda et al [14] reported in their study. Kabir et al [4] and Ubani et al [15] reported moderate to high estimates of repeatability in linear body measurements in broiler chickens.…”
Section: Body Weight and Linear Body Measurements At 4 Weeks Of Agecontrasting
confidence: 85%
“…The moderate to fairly high heritability and repeatability estimates obtained at 4 weeks for both sexes showed that environmental influence on these traits was reduced compared to the results obtained at 2 weeks of age. The heritability estimates obtained in this study were higher than what Sanda et al [14] reported in their study. Kabir et al [4] and Ubani et al [15] reported moderate to high estimates of repeatability in linear body measurements in broiler chickens.…”
Section: Body Weight and Linear Body Measurements At 4 Weeks Of Agecontrasting
confidence: 85%
“…Negative genetic and phenotypic association observed between these traits in both male and female lines could be attributed to the presence of additive and maternal gene effect for these traits. Sanda et al (2014) reported negative genetic and phenotypic correlations between egg weight and egg production up to 280days. The result of this work further corresponds with the findings of Sulaiman, (2022).…”
Section: Egg Weight With Egg Production Up To 280 Daysmentioning
confidence: 99%
“…By so doing, it reduces the interdependency or multicollinearity among independent variables which has been shown to be associated with unstable estimates of regression coefficients (Keskin et al 2007;Yakubu et al 2009) that reduces the accuracy of prediction (Chatterjee et al 2000). The reliability of prediction is reported to depend on positive or negative linear relationship between the dependent variable and the predictors (Semakula et al, 2011;Ojedapo, 2012;Sanda et al 2014) as well as the magnitude of the coefficient of determination. The coefficient of determination explains the total variation in a dependent variable that is accounted for by the explanatory variables or predictors in a linear regression model (Agomy et al 2015).…”
Section: Introductionmentioning
confidence: 99%